Compaction characteristics and penetration resistance of poultry-litter-amended agricultural soils - Okunade, David; Raphael, Davids (Open Access, 2020)
Compaction characteristics and penetration resistance of five southwestern Nigeria agricultural soils amended with poultry litter were investigated. Poultry litter was added to the soil samples at four moisture levels of 6, 9, 12, 15 % weight basis to raise the organic matter content to 2, 4 and 6 % dry mass basis and then later subjected to three levels of compaction blows (5,15 and 25 blows) using a standard proctor hammer in a cylindrical mould. Dry densities and the corresponding moisture content were measured at the different compaction loads. Penetration resistance was measured using the cone penetrometer. Results show that dry bulk density increased with increase in compaction load (5 to 25 blows) from 1.78 to 1.91, 1.68 to 1.88, 1.36 to 1.52, 1.48 to 1.70, and 1.47 to 1.78 gcm-3 but reduced with increasing poultry litter levels (0-6% weight basis) from 1.91 - 1.90, 2.08 - 1.99, 1.74- 1.71, 1.88- 1.78and 1.96- 1.82 gcm-3 for Apomu, Egbeda, Iwo, Oba and Ondo soil series respectively. The penetration resistance reduced with increased load from 50.1- 44.5, 46.8- 44.0, 49.6- 44.0and 39.5- 36.1 N for Egbeda, Iwo, Oba and Ondo soil series respectively. The soil behaviour was not affected by the differences in soil series. These results show that soil compaction, litter application and penetration resistance are interrelated in their influences on soil dry bulk density and moisture content.
Earth and Environmental Science 445 (2020) 012025
Keywords: STEM; Obafemi Awolowo University; soil dry bulk; Poultry litter; proctor hammer; cylindrical mould; penetrometer